Pro‐angiogenic TIE‐2‐expressing monocytes/TEMs as a biomarker of the effect of sorafenib in patients with advanced hepatocellular carcinoma. Issue 5 (8th June 2017) - Shoji, Hirotaka; Yoshio, Sachiyo; Mano, Yohei; Doi, Hiroyoshi; Sugiyama, Masaya; Osawa, Yosuke; Kimura, Kiminori; Arai, Taeang; Itokawa, Norio; Atsukawa, Masanori; Aoki, Yoshihiko; Fukai, Moto; et al.
Abstract : Sorafenib, a multi‐kinase inhibitor, inhibits tumor angiogenesis and is the first‐line systemic therapy for patients with advanced hepatocellular carcinoma (HCC). However, due to its limited effects and frequent occurrence of side effects, biomarkers are needed to predict the effects of sorafenib. We considered the possibility of using TIE‐2‐expressing monocytes (TEMs) to predict the response in sorafenib‐treated patients with advanced HCC. TEMs serve as a diagnostic marker of HCC and are related to angiogenesis. We analyzed 25 advanced HCC patients and prospectively evaluated TEMs before (Pre TEMs) and at 1 month after initial therapy (T1m TEMs). The radiologic response was evaluated by modified Response Evaluation Criteria in Solid Tumors (mRECIST). Median survival time (MST) was significantly longer in the partial response/stable disease (PR/SD) group (21.8 months) than in the PD group (8.7 months). ΔTEMs (changes of T1m TEMs compared to Pre TEMs) were significantly lower in the PR/SD group than in the PD group. MST of the ΔTEMs low group (14.2 months) was significantly longer than that of the high group (8.7 months). Univariate and multivariate Cox regression analyses showed that ΔTEMs [hazard ratio (HR) = 8.53, 95% confidence interval (CI) = 1.51–48.16, p = 0.015] and Child‐Pugh class (HR = 5.59, 95% CI = 1.06–29.63, p = 0.043) were independently associated with overall survival. Our results suggest that ΔTEMs could serve as a biomarker for predicting radiologic response and overall survival in sorafenib‐treated patients with advanced HCC. Abstract : What's new? Sorafenib is the first‐line systemic therapy for patients with advanced hepatocellular carcinoma (HCC), but it has limited effects and frequent side effects. This prospective pilot study evaluated the feasibility of using TIE‐2‐expressing monocytes (TEMs)—a diagnostic marker of HCC—as a predictive biomarker for sorafenib response in HCC patients, identifying TEMs frequency changes for the first time. ΔTEMs–the change in TEMs frequency after 1 month of treatment compared to pre‐treatment–reflected the radiologic response. ΔTEMs were independently associated with overall survival. ΔTEMs could thus serve as a biomarker for predicting the effect of sorafenib treatment in advanced HCC patients.